2022
DOI: 10.22376/ijpbs/lpr.2022.12.6.sp25.l28-33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Suryanamaskar Practices with and Without Yoga Nidra On Stress Among High School Students- A Randomized Controlled Trial

Abstract: Stress is the dynamic connection that exists between an individual and environment where a stimulus (whatever it is) disrupts a person's homeostasis, causing him or her to react to the circumstances with all resources available. The purpose of this study was to determine the effect of suryanamaskar practises with and without yoganidra on stress levels in high school students. It was hypothesised that the influences of suryanamaskar practises with and without yoga nidra would cause significant differences in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It's clear from their studies that medical students adopt strategies to overcome stress. The same authors 13 have also shown that combined yoga and Surya namaskar is extremely useful in combating students' stress. The remembrance anxiety in our study has the highest score, which needs to be addressed in the type of teaching and learning.…”
Section: Anxiety Levelsmentioning
confidence: 92%
“…It's clear from their studies that medical students adopt strategies to overcome stress. The same authors 13 have also shown that combined yoga and Surya namaskar is extremely useful in combating students' stress. The remembrance anxiety in our study has the highest score, which needs to be addressed in the type of teaching and learning.…”
Section: Anxiety Levelsmentioning
confidence: 92%